Idiopathic intracranial hypertension associated with mild traumatic brain injury in a pediatric patient – Case report - Pereira, Carlos Umberto; Feitosa, Stephanie Chagas; Lima, Alyne Andrade (Arquivos brasileiros de neurocirurgia, 2013)
Abstract Mild head injury has been described as rare cause of idiopathic intracranial hypertension (IIH). In the presence of IIH, initial treatment is clinical and surgical treatment, such as lumboperitoneal shunt. Most cases have a good prognosis. The patient have 9-year-old male, went to the emergency room with a history of accidental fall, presenting headache, vomiting and blurred vision. Physical examination showed good overall condition. Neurological examination: normal. Fundoscopy: incipient bilateral papilledema. Normal cranial CT. The general picture suggested by exclusion of other causes IIH diagnosis. He underwent symptomatic treatment with acetazolamide, painkillers and rest. Discharged from the hospital on the eighth hospital day with no complaints being referred for outpatient treatment.